A novel recombinant avian leukosis virus isolated from gamecocks induced pathogenicity in Three-Yellow chickens: a potential infection source of avian leukosis virus to the commercial chickens. (23rd September 2019) - Wang, Peikun; Shi, Mengya; He, Chengwei; Lin, Lulu; Li, Haijuan; Gu, Zhanming; Li, Min; Gao, Yanli; Huang, Teng; Mo, Meilan; Wei, Tianchao; Wei, Ping
ABSTRACT: One natural recombinant avian leukosis virus (ALV ) strain GX14DJ3–18 was isolated from a native gamecock by DF-1 cell culture and identified with Polymerase Chain Reaction (PCR ), immunofluorescence assay and the viral genome's nucleotide sequencing. This strain was revealed as a novel recombinant virus with nucleotide sequence similarities of 95.4% Long Terminal Repeated (LTR ), 95.8% 5′, UTR, 97.9% gag, and 92.9% 3′untranslated regions (UTR) in ALV-J. Also we found sequence similarities of 99.3% pol and 99.0% gp37 in ALV-E, and 89.9% gp85 in ALV-A. The simulated congenital infection with GX14DJ3–18 in Three-Yellow chickens exhibited a significant negative effect on the development of immune organs ( P < 0.05). Also, lower antibody responses were found to vaccinations with the commercial vaccines of Newcastle disease virus and with subtypes H5 and H9 of avian influenza virus ( P < 0.05). The incidence of tumor or tumor-like lesions in the challenged birds was 14.28% (5/35), while none were observed in the un-challenged control group (0/35). These results suggested that GX14DJ3–18 is a novel recombinant ALV that can induce pathogenicity in the commercial Three-Yellow chickens. We speculated that cross-provincial sales of gamecocks in which ALVs have not been eradicated thoroughly might be a potential route for the transmission of ALVs to commercial chickens.